(untitled) (Colombia Medica, 2018)
Background: The Cali Population Cancer Registry (RPCC) has been in continuous operation since 1962 with the objective of producing valid statistics on the incidence of cancer, its patterns, trends and survival rates. Methods: During the period 2008-2012, 23,046 new cases were registered and during 2011-2015 there were 12,761 cancer deaths. The trend of the rates was described with the APC average annual change rate and with the Joinpoint analysis. We analyzed the individual data of 38,671 adults (15-99 years) diagnosed with cancer between 1995-2009, and we calculated the standardized net survival by age for the 14 most common cancer body sites, using the Pohar-Perme method. Results: Prostate and breast cancer were the first cause of cancer morbidity. The incidence rates in these susceptible to early detection, tumors stabilized after decades of growth, while an increase in the incidence of colon cancer and papillary thyroid carcinoma was observed. The incidence rates of cervical and stomach cancer, conditions related to infectious agents, decreased, although the number of absolute cases increased, due to the growth and aging of the population. Gastric cancer was responsible for the highest number of cancer deaths. The types of cancer related to tobacco consumption (lung, oral cavity, esophagus, pancreas, urinary bladder) showed low numbers and a tendency to decrease. During the period 2000-2004, the 5-year net survival improved for cancers of the breast, cervix, prostate, melanoma and thyroid, although in the period 2005-2009 a stagnation was observed. In stomach, liver and lung cancer, the 5-year net survival was less than 15%. The 5-year overall survival in children was 51.0% (95% CI: 47.5, 54.3) and in adolescents 44.6% (95% CI: 36.0, 52.8). Comment: RPCC has been an advisor to the Colombian government in the evaluation of CPRs in the country and its data have contributed significantly to different aspects of cancer control in Colombia.